Genetic diversity and molecular epidemiology of the T strain of Plum pox virus. (2nd January 2019) - Teber, S.; Ceylan, A.; Gürcan, K.; Candresse, T.; Ulubaş Serçe, Ç.; Akbulut, M.; Kaymak, S.; Akbaş, B.
Abstract : Very limited information is available on the origin, diversity and evolution of Plum pox virus (PPV) 'Turkey' (T) strain. Phylogenetic analyses based on partial sequences of 421 isolates and complete genome sequences of 57 isolates, representing the geographical distribution of PPV‐T in Turkey, revealed the existence of several monophyletic and, in some cases, geographically limited groups within the PPV‐T strain (Ankara‐Konya1‐Kayseri, Ankara‐Balkan, Istanbul, Konya2 and Balkan). PPV‐T diversity (0.018%) was found to be greater than that of PPV strains D and Rec but lower than that of the M strain when including the newly described and divergent M‐Istanbul isolates, suggesting a long evolutionary history for PPV‐T. The European part of Turkey in the Balkans, close to Bulgaria where PPV was identified for the first time, appears as a likely centre of origin for PPV‐T isolates. The colonization of various parts of Turkey by diverse isolates from that region, followed by secondary local spread, is the most likely scenario for the diffusion of PPV‐T in Turkey.